Oxidative Stress, Inflammation, and Altered Lymphocyte E-NTPDase Are Implicated in Acute Dyslipidemia in Rats: Protective Role of Arbutin - Reem S. Alruhaimi; Omnia E. Hussein; Sulaiman M. Alnasser; Mousa O. Germoush; Meshal Alotaibi; Emad H. M. Hassanein; Mohamed El Mohtadi; Ayman M. Mahmoud (MDPI AG, 2024)
Background/Objectives: Dyslipidemia is frequently linked to various disorders, and its clinical relevance is now recognized. The role of inflammation and oxidative stress (OS) in dyslipidemia has been acknowledged. This study assessed the potential of arbutin (ARB) to prevent dyslipidemia and its associated OS and inflammation in rats with acute hyperlipidemia. Methods: Rats received ARB orally for 14 days and a single intraperitoneal injection of poloxamer-407 on day 15. Results: Poloxamer-407 elevated circulating cholesterol (CHOL), triglycerides (TG), very low-density lipoprotein (vLDL), and LDL, and reduced high-density lipoprotein (HDL)-C and lipoprotein lipase (LPL). ARB ameliorated the circulating lipids and LPL, and suppressed 3-hydroxy-3-methylglutaryl CoA reductase (HMGCR) in rat liver and in vitro. Fatty acid synthase (FAS) in rat liver and its in vitro activity were suppressed by ARB, which also upregulated the LDL receptor (LDL-R) and ABCA1, and had no effect on ABCG5 and ABCG8 mRNA. ARB ameliorated liver malondialdehyde and nitric oxide and enhanced antioxidants in rats with dyslipidemia. Liver NF-κB p65 and blood inflammatory cytokines were increased in dyslipidemic rats, effects that were reversed by ARB. Moreover, ARB effectively suppressed lymphocyte E-NTPDase and E-ADA activities in dyslipidemic rats. The biochemical findings were supported by in silico data showing the affinity of ARB to bind LDL-R PCSK9 binding domain, HMGCR, FAS, and E-NTPDase. Conclusions: ARB possessed anti-dyslipidemia, anti-inflammatory, and antioxidant effects mediated via the modulation of CHOL and TG synthesis, LPL, lymphocyte E-NTPDase and E-ADA, and cytokine release in rats. Thus, ARB could be an effective agent to attenuate dyslipidemia and its associated OS and inflammation, pending further studies as well as clinical trials.